Strategi Guru Matematika dalam Menciptakan Suasana Belajar yang Kondusif (Aljabar : Jurnal Ilmuan Pendidikan, Matematika dan Kebumian, 2025)
Learning mathematics not only focuses on mastering concepts and calculation skills, but also requires creating a conducive learning environment so that students can think critically, logically, and creatively. A conducive learning environment plays a crucial role in fostering student motivation and active engagement, making the success of the learning process highly dependent on the strategies implemented by the teacher. This research aims to describe mathematics teachers' strategies in creating a conducive learning environment thru the application of active and contextual learning strategies. The method used is library research, which involves collecting and reviewing various scientific sources such as books, journals, and academic articles relevant to the research topic. The research results indicate that active learning strategies are able to increase student participation, strengthen reasoning abilities, and foster learning motivation. Teachers play an important role as facilitators, motivators, mediators, and evaluators, directly influencing the learning climate in the classroom. Contextual learning strategies like REACT (Relating, Experiencing, Applying, Cooperating, Transferring) have proven effective in connecting mathematical concepts with students' real-life experiences and creating a fun and meaningful learning environment. In addition, humanistic classroom management, the use of technology, and adapting learning to students' different abilities are supporting factors in achieving a conducive learning environment. The implications of this research indicate that the success of mathematics learning is not solely determined by the methods used, but also by the teacher's ability to build positive relationships with students and create an interactive, adaptive learning environment that optimally fosters students' potential development.